Validation of BRCA testing on cytologic samples of high‐grade serous carcinoma. Issue 11 (22nd June 2021) - Lou, Si Kei; Grenier, Sylvie; Care, Melanie; McCuaig, Jeanna; Stockley, Tracy L.; Clarke, Blaise; Ruff, Heather M.; Boerner, Scott L.
Abstract : Background: Testing for BRCA1/2 gene alterations in patients with high‐grade serous carcinoma (HGSC) is a critical determinant of treatment eligibility for poly(adenosine diphosphate‐ribose) polymerase inhibitors in addition to providing vital information for genetic counselling. Many patients present with effusions necessitating therapeutic drainage, and this makes cytologic specimens (CySs) the initial diagnostic material for HGSC, often before histologic sampling. Initiating somatic BRCA testing on a CyS allows the BRCA status to be determined sooner, and this affects clinical management. Methods: Retrospectively, 8 cases of formalin‐fixed, paraffin‐embedded (FFPE) CySs of peritoneal or pleural fluid from patients with HGSC and known BRCA1/2 alterations previously established by the testing of FFPE surgical specimens (SpSs) underwent next‐generation sequencing (NGS). Prospectively, 11 cases of peritoneal or pleural fluid from patients with HGSC but an unknown BRCA1/2 status underwent NGS with fresh, alcohol‐fixed, and FFPE CySs, and they were compared with subsequent NGS on 4 SpSs. Results: CySs yielded high‐quantity and high‐quality DNA for NGS analysis when sufficient tumor cellularity was present. Fresh, alcohol‐fixed, and FFPE CySs were all suitable for NGS and provided identical NGS results. SpS and CyS BRCA testing was concordant in 10 of 12 cases. The 2 discordant cases showed low tumor cellularity and quality in the CyS and the SpS, respectively. Conclusion: Effusion CySs of HGSC are excellent sources for NGS testing for BRCA1/2 genetic alterations when sufficient tumor cellularity is present. Fresh, alcohol‐fixed, and FFPE CySs are equivalent for NGS of BRCA1/2 . NGS testing of HGSC CySs demonstrates good concordance with SpSs for the BRCA1/2 status. Abstract : BRCA molecular testing of cytologic specimens of high‐grade serous carcinoma shows good concordance with matched surgical specimens. This has implications for treatment eligibility for poly(adenosine diphosphate‐ribose) polymerase inhibitors and for the triaging of germline testing.